2005
DOI: 10.1021/om0501069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of a Stable 1,3-Dihydrotriphosphane and Its Thermal Decomposition Leading to the Formation of the Corresponding Phosphine and Diphosphene

Abstract: Treatment of dichloroferrocenylphosphine with two molar amounts of a lithium phosphide bearing a 2,4,6-tris[bis(trimethylsilyl)methyl]phenyl (denoted as Tbt) group afforded the corresponding 1,3-dihydro-2-ferrocenyltriphosphane [1; (TbtHP) 2 PFc, Fc ) ferrocenyl] as a mixture of three diastereomers in 73% yield. In sharp contrast to the previously reported 1,3-dihydrotriphosphanes [(RHP) 2 PR, R ) Ph, t-Bu], 1 was quite stable toward air and moisture either in the solid state or in solution at ambient temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
2
11
0
2
Order By: Relevance
“…[13] Only 1,3-dihydrotriphosphines of the type (RPH) 2 PR' with bulky substituents (R = 2,4,6-[(Me 3 Si) 2 CH] 3 C 6 H 2 , R ' = (C 5 H 4 )CpFe (Cp = C 5 H 5 ), [14] and R = R' = tBu [15] ) are stable at room temperature, usually forming mixtures of three diastereomers. Significantly, the isolated triphosphine 5 shows only the A 2 M spin system of one diastereomer in the 31 P NMR spectrum, whereas for the arsadiphosphine 6 an A 2 and an AM spin system of a 1:1 mixture of two diastereomers have been found.…”
Section: Dedicated To Professor Martin Jansen On the Occasion Of His mentioning
confidence: 99%
“…[13] Only 1,3-dihydrotriphosphines of the type (RPH) 2 PR' with bulky substituents (R = 2,4,6-[(Me 3 Si) 2 CH] 3 C 6 H 2 , R ' = (C 5 H 4 )CpFe (Cp = C 5 H 5 ), [14] and R = R' = tBu [15] ) are stable at room temperature, usually forming mixtures of three diastereomers. Significantly, the isolated triphosphine 5 shows only the A 2 M spin system of one diastereomer in the 31 P NMR spectrum, whereas for the arsadiphosphine 6 an A 2 and an AM spin system of a 1:1 mixture of two diastereomers have been found.…”
Section: Dedicated To Professor Martin Jansen On the Occasion Of His mentioning
confidence: 99%
“…Although Niecke et al reported the synthesis of Mes * P PFc, it was unstable and difficult to treat under ambient conditions due to its ready self-dimerization [33]. By contrast, we have reported the synthesis and isolation of TbtP PFc (1a), which was found to be thermally and photochemically stable without any dimerization, and its crystalline structure and redox behavior have been disclosed [10,11]. The first stable ferrocenyldiphosphene can be a useful building block for ferrocenyl-substituted heterocycles, such as chalcogenadiphosphiranes.…”
Section: Introductionmentioning
confidence: 78%
“…Elemental analyses were carried out at the Microanalytical Laboratory of the Institute for Chemical Research, Kyoto University. TbtPH 2 [19] and b-enaminoketone 5 [16] were prepared according to the reported procedures.…”
Section: General Experimental Detailsmentioning
confidence: 99%